Perbandingan Hukum Indonesia dan Malaysia: Reformulasi Kebijakan Aborsi Akibat Tindak Pidana Perkosaan di Indonesia - Mardin, Nurhayati; Haryanti, Tuti; Kharismawan, Adiguna (DIKTUM: Jurnal Syariah dan Hukum, 2022)
The purpose of this paper is to compare the provisions regarding abortion of pregnancies resulting from rape according to the law in Indonesia and Malaysia, to obtain an overview to reformulate legal rules regarding abortion of pregnancies due to rape in Indonesia which are seen as defiance of the right to life. The method in this research is normative juridical research with statutory and comparative approaches and using primary and secondary legal materials. The results of this study indicate that the law in Indonesia legalizes abortion as a result of rape followed by certain conditions. In contrast to Malaysia, which does not strictly state the permissibility of abortion as a result of rape in its statutory regulations, however, in practice, abortion, for this reason, may be carried out when there are indications of serious, dangerous trauma based on the assessment of a doctor or a team of competent doctors. On the other hand, in Indonesia, the reason for abortion as a result of rape is legalized in the provisions of the Health Law with several conditions regulated in the Government Regulation on Reproductive Health. Therefore, the legalization of abortion for pregnancies resulting from the criminal act of rape needs to be reformulated concerning human rights.